Transformation of nanomaterials and its implications in gut nanotoxicology - Setyawati, Magdiel Inggrid (2021)
Ingestion of engineered nanomaterials (ENMs) is inevitable due to their widespread utilization in the agrifood industry. Safety evaluation has become pivotal to identify the consequences on human health of exposure to these ingested ENMs. Much of the current understanding of nanotoxicology in the gastrointestinal tract (GIT) is derived from studies utilizing pristine ENMs. In reality, agrifood ENMs interact with their microenvironment, and undergo multiple physicochemical transformations, such as aggregation/agglomeration, dissolution, speciation change, and surface characteristics alteration, across their life cycle from synthesis to consumption. This work sieves out the implications of ENM transformations on their behavior, stability, and reactivity in food and product matrices and through the GIT, in relation to measured toxicological profiles. In particular, a strong emphasis is given to understand the mechanisms through which these transformations can affect ENM induced gut nanotoxicity.